PTH-159 The relevance of lymph node metastases in the proximal field of the chest in patients with adenocarcinoma of the gastro-oesophageal junction treated with neoadjuvant therapy followed by transthoracic oesophagectomy. (22nd June 2015) - Lagarde, SM; Jagadesham, VP; Gisbertz, SS; Immanuel, A; van Berge Henegouwen, M; Griffin, M
Abstract : Introduction: The prognosis of gastroesophageal junction adenocarcinoma is unquestionably related to the extent of nodal involvement. Not only the amount of positive lymph nodes but also the location of postive nodes negatively influence survival. Earlier small studies revealed a poor survival for patients with positive nodes in the proximal field of the chest when treated with surgery alone. It is thus far unknown what the relevance of these nodes is after neoadjuvant therapy. The aim of the present study was to identify the incidence and prognostic significance of lymph node metastases in the proximal part of the chest in patients who underwent a transthoracic oesophagectomy after neoadjuvant therapy. Method: From a prospectively collected database, a consecutive series of patients in two high volume centres in Europe was analysed. All patients with potentially curable adeno carcinoma of the gastro-oesophageal junction were treated with neoadjuvant chemo (radiation)therapy therapy followed by transthoracic oesophagectomy and two-field lymphadenectomy. Results: Between January 2000 and September 2013 a consecutive series of 208 patients underwent an oesophagectomy after neoadjuvant therapy for adenocarcinoma of the gastro-oesophageal junction. 80 (38.5%) patients had no evidence of lymph node metastases (N0). There were 128 patients (61.5%) with positive nodes (N1=41 (19.7%), N2=44 (21.2%), N3=43 (20.7%)). Of the node positive patients, 25 (19.5%) had positive nodes in the proximal field of the chest (paratracheal, subcarinal, bronchial and aorto-pulmonary window lymph nodes). More advanced N-stage was significantly associated with positive nodes in the proximal field of the chest (p < 0.001). Median survival was significantly (p = 0.003) worse for patients with positive nodes in the proximal part of the chest (12.4 months (95% CI: 11.4–13.32)) compared with patients with positive nodes on other locations (28.3 months (95% CI: 22.7–33.9)). Conclusion: Lymph node metastases in the proximal part of the chest in patients is a common phenomonemon and a sign of advanced disease. Radical surgical resection can only be achieved with an extended transthoracic resection. Even after neoadjuvant therapy followed by transthoracic resection long-term survival is poor. Disclosure of interest: None Declared.